FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN NON KEUANGAN - VENY MEILINDA; NICKEN DESTRIANA (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this research was to determine the effect of the variable return on asset, the ratio of market value to book value of equity, the proportion of profit margin before interest, taxes, and depreciation, rate of return on sales, debt to equity ratio, current ratio, total asset turnover ratio, and working capital turnover ratio to the stock return. The number of samples consist of 78 listed non-financial company in Indonesia Stock Exchange during the period 2013-2016 using purposive sampling method. The examination of the data uses multiple regression analysis. The result of this research showed that the variables return on asset, debt to equity ratio, and working capital turnover ratio affected stock returns, while the other variables such as the ratio of market value to book value of equity, the proportion of profit margin before interest, taxes, and depreciation, rate of return on sales, current ratio, and total asset turnover ratio have no effect to stock returns.